(3GdQSGdI GdjeGfjIs - (3YHO GdYdje Hf CHj GdbGSe Hf YKeGf Hf GbHGd Gdjefj GdMfajs
(3ChdgG (B:s
(3GdMeO ddg Gdedc GdHQ GdLhGO GdPi aQV GdLgGO Ydi GdYHGO EjLGHkG hEdRGekG s
(3BNQgG (B:s
(3hYf CHj gQjQI QVi Gddg Yfg Yf QShd Gddg Udi Gddg Ydjg hSde bGd ef eGJ eQGHWkG ai SHjd Gddg CLQi Ydjg CLQ Yedg GdUGdM GdPi cGf jYed hHYKg Gddg jhe GdbGjeI s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3aQhSjI JjehQ (B88) s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs